Interferensi Bahasa Daerah Dalam Kolom "Nusantara" Koran Kompas Edisi Februari - April 2017 Dan Diimplementasikan Dalam Pembelajaran Bahasa Indonesia Di SMP - Cahyati, Suci; , Dra. Atiqa Sabardila, M. Hum (2017)
This study deals with interference of regional languages in the "Archipelago" Kompas newspaper. The aim is to describe the vocabulary of the vernacular and the function of the use of regional languages in the "Archipelago" Kompas newspaper editions from February to April, 2017, describing the function of the use of regional languages in the "Archipelago" Kompas newspaper editions from February to April, 2017, describing the relationship the use of the interference of regional languages by learning Indonesian in junior high school. This research uses descriptive qualitative research method. Descriptive qualitative research is research that aims to illustrate or describe the reality. In this study using the method refer to the method followed note. The process is the use of interference listened to in the column "Archipelago" Kompas newspaper editions from February to April 2017. In this study, the technique used is an orthographic unified analysis techniques. Mechanical unified orthographic writing in the form of interference classing the local language in the "Archipelago" Kompas newspaper editions from February to April 2017. Through the analysis of the data will be collected interference of regional languages in the "Archipelago". The results of this study found 82 data using regional language interference. The function of the use of regional languages in the "Archipelago" Kompas newspaper editions from February to April 2017 as a symbol of regional identity, the symbol of regional pride, and means of transportation in the area around the family and society.